Netflix viewing habit, grammatical competence, and academic self-efficacy of Selected Senior High School Students In Tagaytay City, Cavite - Faminiano, Maria Teresa; Yango, Antonio R. (Technium Social Sciences Journal, 2023)
Grammatical competence is the knowledge of and ability to use a language’s grammatical resources. Understanding and communicating meaning across generations, as well as being able to recognize properly constructed sentences that adhere to these rules (Kusumawardani & Mardiyani, 2018). On the other hand, students who have high self-esteem are more likely to achieve their goals and cope better with life’s challenges, whereas those who have low self-esteem are more likely to become isolated. One of the psychological issues that all students face is issues with self-esteem. Self -esteem influences one’s self-efficacy. Furthermore, watching English movies, particularly those with English subtitles, will improve one’s vocabulary and speaking ability (Pratiwi & Ayu, 2020). However, despite the numerous studies that investigated language learning and mastery of grammar, no study was conducted yet regarding the relationship between Netflix viewing habits, grammatical competence, and academic self-efficacy of senior high school students specifically in the local setting. Hence, the researcher was motivated to conduct a study to determine the Netflix viewing habits, grammatical competence, and academic self-efficacy of the selected senior high school students from public schools in Tagaytay City. The findings of this study could serve as a guide to English teachers and administrators in designing innovative strategies that will enhance the students’ grammatical skills and academic self-efficacy taking into consideration the integration of watching English movies in the teaching-learning process specifically in language class. The researcher utilized descriptive-correlational method of research with the help of survey questionnaire as the main source of data. Statistical method utilized to give credence and reliability to the work. Based on the findings of the study, the study conclusions were drawn: Majority of the respondents watch Netflix 1-2 times week; 45.70 percent of them watch for 3-4 hours a day; and 21.20 percent of them prefer to watch drama; The respondents has satisfactory level of grammatical competence and high level of academic self-efficacy. In addition, the more frequently the students watch Netflix ,the higher their level of grammatical competence. Moreover, the more frequently the respondents watch Netflix, the higher their level of academic self-efficacy. In addition, the higher the respondents’ level of grammatical competence, the higher their level of academic self-efficacy Finally, the independent variable Netflix viewing habits in terms of, duration and grammatical competence are drivers of students’ level of academic self-efficacy, which further means that the students’ Netflix viewing habits and grammatical competence determine their academic self-efficacy.